Transformation of Understanding of Sexuality in High School Sociology Textbooks in Indonesia - Sofia, Sofia; Wardana, Amika; Torro, Supriadi; Nurazizah Rahmi R (Equilibrium: Jurnal Pendidikan, 2026)
The increasing cases of sexual violence, harassment, and gender-based bullying among adolescents raise questions about the extent to which sexuality education has been integrated into the formal education system. As one of the primary learning resources, textbooks play an important role in shaping students’ understanding of sexuality and social relations. However, the representation of sexuality in school textbooks remains relatively underexplored. This study aims to analyze the representation and transformation of sexuality discourse in Indonesian senior high school sociology textbooks across three curriculum periods: the School-Based Curriculum (KTSP), the 2013 Curriculum, and the Merdeka Curriculum. This research employs a qualitative approach using content analysis of 18 senior high school sociology textbooks to identify how sexuality is represented within the contexts of sexual violence, gender relations, and social deviance. The findings indicate that discussions of sexuality in textbooks remain limited and are generally positioned as a minor part of the topic of social deviance. Sexual violence is mostly presented in a descriptive manner without comprehensive discussion of its psychosocial impacts or preventive strategies. This study contributes by demonstrating how textbook discourse reproduces a limited understanding of sexuality and highlights the importance of integrating more comprehensive sexuality education into sociology learning materials.